Optimizing Officer and Cadre Satisfaction with the Family Posyandu Reporting System with (Si Lina Gesit) Google Spreadsheet Online Information System at the Klampis Health Center - M. Suhron; Fina Marantina; M. Hasinuddin; Novi anggraeni (Universitas STRADA Indonesia, 2025)
Background: Posyandu is a form of Community-Resourced health effort that is managed, by and for the community to empower it and make it easier for the community to obtain health services, especially in the reporting system carried out by village midwives and cadres. Purpose: Analyzing the satisfaction of officers and cadres with the Family Posyandu Reporting System using (Si Lina Gesit) Google Spreadsheet online information system at the Klampis Community Health Center. Methods: Type of experimental research: pre-post test One Group Design, sampling technique with purposive sampling, sample size of 44 officers and cadres analyzed statistically using the Wilcoxon test. Results: There are differences in the Tangible, Reliability, Responsiveness, Assurance and Empathy indicators between before and after the intervention was given, apart from that, based on the Wilcoxon Test analysis on satisfaction, the P value was (0.000) < α (0.05). Conclusion: There is a difference in satisfaction between before and after the intervention was given to cadres at the Klampis Community Health Center.